Innovative materials and systems for energy harvesting applications - Mescia, Luciano, 1973-; Losito, Onofrio, 1969-; Prudenzano, Franceso, 1964- (Advances in environmental engineering and green technologies (AEEGT) book series., 2015)
"This book reports on some of the best tools and technologies available for powering humanity's growing thirst for electronic devices, including piezoelectric, solar, thermoelectric, and electromagnetic energies"--